Exchange rate pass-through in the New Member States of the European Union - Bajo-Rubio, Oscar; Maria-Dolores, Ramon (Kurs walutowy a inflacja w krajach Europy Środkowo-Wschodniej. Analiza empiryczna, 2011)
In this paper, we study the extent of exchange rate pass-through (ERPT) of foreign to domestic prices, for the imports from the euro area of five New Member States of the European Union (i.e., Hungary, Poland, Czech Republic, Slovak Republic, and Romania). To that end, we use data on import unit values for nine different product categories, from 2000 to 2007. In addition, we also examine the influence on ERPT of several macroeconomic factors (average inflation, the exchange rate regime, or the degree of openness of the countries)
Ekonomia = Economics, 2011, Nr 2 (14), s. 88-94
Keywords: exchange rates; pass-through; monetary union; panel cointegration